‘A sneaky bit of stalking’: Young people, social network sites, and practices of online surveillance - Milivojević Sanja; Crofts Thomas; Lee Murray; McGovern Alyce (Temida, 2018)
This article maps the important albeit under-researched relationship between young people, social network sites, and surveillance practices they encounter or engage with in their digital lives. Based on original empirical research, this article unpacks the complexities of young people’s digital identities, and explores strategies of surveillance, covert and overt, that young people are subjected to and perform on a daily basis. Often justified through risk-based crime prevention narratives, such intrusive strategies scrutinise young people in order to anticipate crime and victimisation on social network sites that has not yet, and might never occur. As such, these strategies are arguably underpinned by pre-crime logics of anticipating and targeting impending crime and victimisation. Importantly, they are increasingly normalised as they are imposed for young people’s “own good”. Yet, as this article demonstrates, young people are aware of such strategies and simultaneously engage in, experience being subject to, and resist surveillance practices.